Financial Development Strategies of Countries: Identifying Priority Financial Instruments - Gospodarchuk, Galina; Zeleneva, Elena (Ital Publication, 2024)
The effectiveness of financial development strategies for countries depends on the methodology used for their formation and implementation. However, a review of the literature reveals that the methodology for implementing these strategies is not fully developed. Therefore, this study aimed to create a methodology for implementing financial development strategies by identifying priority financial instruments. The study utilized rule-based judgment, iterative methods, and the